Biological and molecular structure analyses of the controls on soil organic matter dynamics - Magrini, K., author; Follett, R. F., author; Conant, R., author; Paul, Eldor A., author; Morris, S. J., author; Lomonosov Moscow State University, Department of Chemistry, publisher (Colorado State University. Libraries, 2008)
The dynamics of soil organic carbon (SOC) are controlled by the interaction of biological, physical, and chemical parameters. These are best measured by a combination of techniques such as long-term field sites with a C3↔C4 plant switch. Acid hydrolysis and 14C- dating measure the mean residence time (MRT) of the resistant fraction. Long-term incubation allows the in situ biota to identify and decompose the labile SOC components. Statistical analysis (curve fitting) of the CO2 release curves, determines the pool size and of the two labile fractions (1). The effect of chemical structure is measured with pyrolysismolecular beam mass spectrometry (py-MBMS). The dynamics of charcoal, clay and silt are measured with both 13C and 14C.
Keywords: 14C; 13C; microbial biomass; pyrolysis mass spectrometry; soil organic matter dynamics